2018
DOI: 10.1016/j.foreco.2018.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest roads on oak trees via cervid habitat use and browsing

Abstract: Roads can affect animals in several ways, by affecting movement, space use, foraging behaviour and mortality. As roads often have a negative effect on populations of birds and mammals, their effects are important for wildlife management. However, the effect of roads differ between different types of roads, and most studies of road ecology have focused on major roads with high traffic intensity, whilst effects of smaller unpaved forest roads in northern ecosystems are less known. We investigated the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 56 publications
4
19
0
Order By: Relevance
“…6). This corresponded to findings of Mathisen et al (2018) who observed higher browsing intensity in the inner reaches of the forest. In addition to the effect of visitors, real seed sources may not have been included in the data.…”
Section: Random Effectssupporting
confidence: 90%
See 1 more Smart Citation
“…6). This corresponded to findings of Mathisen et al (2018) who observed higher browsing intensity in the inner reaches of the forest. In addition to the effect of visitors, real seed sources may not have been included in the data.…”
Section: Random Effectssupporting
confidence: 90%
“…These areas are visited for recreational use and game may avoid these areas as a result. Mathisen et al (2018) found that proximity to forest roads affects the intensity of browsing of oak as red deer (Cervus elaphus L.) and roe deer (Capreolus capreolus L.) avoid these areas. A lower local game density can, therefore, lead to a higher regeneration density in the vicinity of cities.…”
Section: Random Effectsmentioning
confidence: 99%
“…High human risk perception in natural areas, by concentrating wild mammals within more densely covered forests that provide more efficient protection to human disturbance, has been suggested to even modify the nitrogen biogeochemical cycle, with the potential for soil eutrophication [66]. Similarly, the avoidance of humans and their infrastructures can intensify forest browsing by ungulates in the less disturbed and more secluded areas, with potential negative impacts on forest dynamics [67]. Both scenarios are in line with our findings that ungulates consistently avoided areas with high rates of human frequentation, possibly resulting in aggregation of herbivores in less disturbed and less accessible areas.…”
Section: Discussionmentioning
confidence: 99%
“…Strand et al 2018). Although some studies indicate that ungulates in forest landscapes avoid minor roads (Laurian et al 2008;Mathisen et al 2018), this is likely due more to higher risk of hunting mortality and predation by large carnivores than to the character of the road surface. Furthermore, the results indicated that shrub as a substrate (or habitat) in fauna passages was avoided by ungulates, although shrub should appear natural and provide shelter and even food (depending, of course, on species), and although shrub in the current cases forms more or less continuous habitat corridors through these passages and thereby connects habitats across the infrastructure.…”
Section: Discussionmentioning
confidence: 99%